Entre fotografias e cavalos: as imagens como potência de fabulação - Oliveira, Renata Cavalcante de (2022)
In “Between Photographs and Horses: Images as a Power of Fabulation”, I present the research that aims at the analysis, experimentation and reflection of eight photographs in which I, my brothers, uncles and nephews are on horses, with the exception of only one in which my grandfather Raimundo appears lifting a piece of meat. I start by presenting the first image that I found in my Portuguese and history books and that stimulated my research. I discuss theories of photography and autofiction, accessing authors such as Didi Huberman, Roland Barthes, Susan Sontag and Doubrowsky. I continue to discuss and relate the photographs to the work of artists such as Aline Motta and Sara Perovic. I joined the images I found in textbooks with other photos I already had at home and creating a visual script with the photographs. This script became the research methodology. Another important decision for the methodology is sharing, sharing the authorship of the works during the master's research with other people. This idea of “doing it together” is present until the end of the research, so I tried to place the original large photographs in the body of the text, so that the reader could highlight, scribble, frame and create new narratives. I carried out four actions during the master's degree: “Classroom”, “Auto-mise-en-scéne”, “Manda Meme” and “Love, death, photography”. In “Classroom”, my students are a fundamental part and have become directors in my creation process. The artist and researcher Naira Ciotti (1999), with her concept of a performer teacher, makes a great contribution to the research at this stage. In “Auto-mise-en-scéne”, I present a work that I made and that is an experiment that allowed me to create new images with reference to mine on the wooden horse. In “Manda Meme”, I propose an action from my personal profile on Instagram, allowing people to interact with the images and build new meanings with the photographs. In “Amor, morte, photography”, I create a joint performance with my mother. I'm building a mediation between who photographs and who is photographed. Bringing the photographs into the classroom was the best thing that ever happened to me. From what the students pointed out, I started experimenting with new creations with the images.